Approach to the child with fatigue: A focus for the general pediatrician - De Nardi, Laura; Lanzetta, Maria Andrea; Ghirigato, Elena; Barbi, Egidio; Gortani, Giulia (Frontiers in Pediatrics, 2022)
Background: Fatigue is a common, nonspecific complaint commonly used to describe various conditions, ranging from a vague, subjective sense of weariness to muscular weakness, fatigability, exercise intolerance or excessive daytime somnolence. Despite its high frequency in the general population, literature addressing the approach to the child with fatigue from a general pediatrician perspective is poor. We herein propose a review of the available evidence on the topic, providing a practical framework to assist physicians in dealing with the issue. Methods: Data were identified by searches of MEDLINE, UpToDate, Google Scholar and references from relevant articles. Articles published between 1990 and 2021 were considered, prioritizing systematic reviews and meta-analyses. Then, an empirically-based model of approaching the tired child was proposed according to our center experience. Results: To correctly characterize the meaning of fatigue reporting, specific clues from history and physical examination should be emphasized. Duration, severity, and the age at onset are to be considered. Then, specific queries about everyday activities, sleep hygiene and social domain could be useful in reaching a specific diagnosis and offering an appropriate treatment. Conclusions: We suggest a pragmatic approach to fatigue in children based on age assessment, targeted questions, physical examination clues, and some laboratory first-level tests. This could provide pediatricians with a useful tool to discriminate the broad etiology of such a complaint, disentangling between psychological and organic causes. Further studies are needed to investigate the predictive value, specificity and sensitivity of this diagnostic workflow in managing the child with fatigue.